2022
DOI: 10.34067/kid.0002632021
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspective on Kidney Transplantation: Argentina

Abstract: This is an Early Access article. Please select the PDF button, above, to view it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…2,3 The kidney is the most commonly donated and transplanted solid organ worldwide. 4 Kidney transplant (KT) is one of the major developments in modern medicine and the best choice for failed kidneys. 5 The first successful KT was performed in 1959 in Louisiana.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The kidney is the most commonly donated and transplanted solid organ worldwide. 4 Kidney transplant (KT) is one of the major developments in modern medicine and the best choice for failed kidneys. 5 The first successful KT was performed in 1959 in Louisiana.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The low percentage of waitlisted patients is similar in Argentina (17%) and the United States (18%), whereas in Australia only 26% of patients with incident end-stage kidney disease from 2006 to 2015 were transplanted or placed on the waitlist list. 3 , 4 , 5 This low percentage likely underestimates the scope of the transplant access problem, because previous work from the United States has suggested that there is a sizable population of patients on dialysis who are never listed for kidney transplant despite having comorbidities and predicted life expectancy that is similar to the waitlist population. 6 Access to transplantation can be affected by medical comorbidities, regional differences in listing practices, and race or ethnicity.…”
mentioning
confidence: 99%